The devil's captain : Ernst Jünger in Nazi Paris, 1941-1944 - Mitchell, Allan, 1933- (Berghahn Books, 2011)
Author of Nazi Paris, a Choice Academic Book of the Year, Allan Mitchell has researched a companion volume concerning the acclaimed and controversial German author Ernst Jünger who, if not the greatest German writer of the twentieth century, certainly was the most controversial. His service as a military officer during the occupation of Paris, where his principal duty was to mingle with French intellectuals such as Jean Cocteau and with visiting German celebrities like Martin Heidegger, was at the center of disputes concerning his career. Spending more than three years in the French capital,